An appropriate fea modeling technique for on-bottom roughness analysis - Witcha Leepipatpaiboon; Chiu, Gregory L.F.; Pornpong Asavadorndeja; Pennung Warnitchai; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Pipeline spanning analysis is the one of critical criteria for pipeline design. An evaluation of an allowable free-span length is required in pipeline design. However, the possible free span for checking against the allowable limit is important as the free span is the unknown value until pipeline already laid. The pipeline will suffer in the buckling effect and overstress if the free span is exceed than the allowable length. On-bottom roughness analysis is a name of computer simulation using for finding the pipeline configuration on the seabed. The simulation is taken care by ABAQUS program. The simulation results depend on several parameters including (i) Analysis boundary conditions, (ii) Type of elements, (iii) Soil modeling technique and (iv) Environmental modeling technique. Variation of these parameters leads to significant divergence of simulation results. The appropriate parameters shall be selected to ensure the simulation result is realistic. This study is to determine the appropriate finite element modeling technique for on-bottom roughness analysis. Three parameters including (i) Analysis boundary conditions, (ii) Type of elements, (iii) Soil modeling technique, were selected as variable in analysis. The appropriate model will be selected by degree of span accuracy, degree of conservative model and suitably run-time and resource. The appropriate model should be accurate and conservative in time and resource limitation. The boundary condition 1 and 4 are the appropriate models especially boundary condition which uses less time and resource for analysis. B33H element is conservative in the pipeline spanning while PIPE31H element is conservative in maximum von mise stress.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Pipelines -- Design and construction